Social Support and a Sense of Purpose: The Role of Personal Growth Initiative and Academic Self-Efficacy - Cai, Jingxue; Lian, Rong (Frontiers in Psychology, 2022)
Objective: Studies have consistently found a positive relationship between social support and a sense of purpose; however, less is known about the underlying mechanisms of this relationship. The present study bridges this gap by proposing and testing a path model illustrating the mediating effects of personal growth initiative and academic self-efficacy on the linkage between social support and a sense of purpose. Method: A total of 2,085 Chinese undergraduates completed the revised versions of the Social Support, Personal Growth Initiative, Academic Self-Efficacy, and Sense of Purpose Scales. Results: The results show that social support, personal growth initiative, and academic self-efficacy were all significantly associated with a sense of purpose. As predicted, personal growth initiative and academic self-efficacy mediated the relationship between social support and a sense of purpose, respectively. The results also support the hypothesized serial mediating effect. Conclusion: Individuals who feel more social support have a higher level of personal growth initiative, their academic self-efficacy is stronger, and their academic self-efficacy further enhances their sense of purpose. Additionally, comparisons among the three indirect effects indicated that the effect of personal growth initiative was significantly greater than those of the other two measures. Thus, it can be concluded that personal initiative plays a greater role in enhancing a sense of purpose. These findings not only help to understand how social support enhances the sense of purpose, but also provide insight into the underlying mechanism.